Unmasking Orphan Students' Deep Psychological Defeat: Membuka Kedok Kekalahan Psikologis Siswa Yatim Piatu - Batoul Jassim Faisal; a. Dr. Sana Abdel Zahra Al-Jamaan (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Psychological defeat significantly impacts individuals' emotional well-being, particularly in vulnerable populations such as orphan students. Existing research often overlooks the nuanced experiences of orphans in secondary education. Specific Background: Orphanhood, encompassing the loss of one or both parents, creates unique psychological challenges that can affect students' emotional and academic performance. This study addresses the gap in understanding how these challenges manifest among orphan students in secondary schools. Knowledge Gap: Despite acknowledging the emotional difficulties faced by orphans, limited research has specifically explored psychological defeat among this group, particularly concerning the impact of parental loss and gender differences. Aims: This research aims to identify and measure the degree of psychological defeat among orphan students in secondary schools in Basra Governorate. The study also seeks to determine if psychological defeat varies by the type of parental loss and gender. Results: The study found that orphan students experience a high level of psychological defeat, with no significant gender differences observed. However, significant variations in psychological defeat were identified based on the type of parental loss (father, mother, or both). Novelty: This research introduces a newly developed scale for measuring psychological defeat tailored to the context of orphan students, filling a critical gap in existing literature. Implications: The findings underscore the need for targeted psychological support and interventions for orphan students, considering the type of parental loss. Recommendations include developing tailored counseling programs and support mechanisms to address the specific needs of these students and mitigate their psychological defeat. Highlights: High psychological defeat in orphan students, regardless of gender. Variations by parental loss type, significant differences found. New scale developed for measuring psychological defeat in orphans. Keywords: Psychological defeat, orphan students, secondary education, parental loss, emotional well-being